Participants' characteristics at ISER-lab in 2020 - Nobuyuki Hanaki; Keigo Inukai; Takehito Masuda; Yuta Shimodaira (Osaka University, Institute of Social and Economic Research (ISER), 2021)
We summarize the experimentally measured characteristics of the regis- tered participants of the experiments conducted at the Institute of Social and Economic Research, Osaka University. Measured characteristics include uid intelligence, risk preference (risk aversion, prudence, and temperance), social value orientation, theory of mind, personality (Big Five and Grit), ability to backward induct, as well as their general trust. We discuss reliability of these measures and correlation among them.
Keywords: C91; D91; 330; Cognitive Ability; Personality; Theory of Mind; Higher OrderRisk Preferences